2010
DOI: 10.1038/nrurol.2010.4
|View full text |Cite
|
Sign up to set email alerts
|

New treatments for chronic prostatitis/chronic pelvic pain syndrome

Abstract: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is a common condition among men of a wide age range, with detrimental effects on quality of life. The etiology, pathogenesis, and optimal treatment of CP/CPPS remain unknown, although progress has been made in these domains in recent years. A wide variety of pharmacologic and nonpharmacologic therapies have been studied in clinical trials, but most have shown limited efficacy in symptom alleviation. CP/CPPS is increasingly viewed as a condition that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 90 publications
(88 reference statements)
0
46
0
3
Order By: Relevance
“…However, in men with CP/CPPS largely unresponsive to medical interventions, greater pain is associated with diminished QoL (28). Therefore, proposing that men with CP/CPPS should wear Physicians currently prescribe a wide range of medications, some of which have studied, and numerous of them have not been studied yet in randomized controlled trials (RCTs), however, none of them has shown high efficacy (29). Many new drugs for CP/CPPS treatment were found to be valueless (30,31), and most commonly used drugs have adverse effects, especially when used in longterm (32).…”
Section: Discussionmentioning
confidence: 99%
“…However, in men with CP/CPPS largely unresponsive to medical interventions, greater pain is associated with diminished QoL (28). Therefore, proposing that men with CP/CPPS should wear Physicians currently prescribe a wide range of medications, some of which have studied, and numerous of them have not been studied yet in randomized controlled trials (RCTs), however, none of them has shown high efficacy (29). Many new drugs for CP/CPPS treatment were found to be valueless (30,31), and most commonly used drugs have adverse effects, especially when used in longterm (32).…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent therapies for CP/CPPS include single or sequential treatments or multimodal approaches with antibacterial, analgesics, and anti-inflammatory drugs, ablockers, and pelvic floor rehabilitation to treat dysfunctional voiding, but very few studies have been performed in which anxiolytic or antidepressant medications, or both, have been used to control psychologic problems. 7 To date, no studies have used duloxetine hydrochloride to modulate pain and changes in the psychoemotional status in patients affected by CP/CPPS.…”
mentioning
confidence: 99%
“…Alternatively, dysfunctional voiding may result in intraprostatic ductal reflux (Hedelin & Fall, 2008). Investigators have found an increased maximal urethral closure pressure and a decreased urinary flow rate in patients with CPPS www.intechopen.com compared with control patients (Strauss & Dimitrakov, 2010). They attributed the high maximal urethral closure pressure to increased adrenergic stimulation in the proximal urethra and bladder neck and proposed that this might cause intraprostatic reflux of urine.…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…Based on these observations they suggested the use of the term "painful male urethral syndrome". Furthermore, spasm of the pelvic floor muscles alone or in combination with bladder neck dysfunction may contribute to chronic pelvic pain (Strauss & Dimitrakov, 2010).…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation